Leadership and Multicultural Environment - Kholilur Rahman; Ahmad Aziz Fanani (INCARE, International Journal of Educational Resources, 2024)
A pesantren is a non-formal educational institution with its own distinctiveness in the sociological and historical context of Indonesia. From the beginning, pesantren were established based on the leadership of a religious figure, supported and trusted by the local community. This research aims to explore and analyze how power and authority contests take place within the pesantren, particularly in the context of leadership at Pondok Pesantren Bustanul Makmur Genteng, led by KH. Muwafiq Amir. The study focuses on three main aspects: the paradigm of power and authority, the perspective of personal virtues, and the multicultural environment that shapes multicultural leadership in the pesantren. This research also seeks to redefine and revise the implementation of existing leadership theories by developing a theoretical framework different from previous studies. The research employs a literature review analysis method. Data collection is conducted through a systematic search of scholarly literature, including articles, journals, and documents that significantly discuss the theme of this study. The leadership of KH. Muwafiq Amir at Pondok Pesantren Bustanul Makmur, Genteng, Banyuwangi, highlights an intelligent adaptation to the local socio-cultural context and multicultural challenges in an urban environment. Although he is not a direct descendant of the pesantren's founder, KH. Muwafiq plays a key role in managing the pesantren through collaborative strategies involving the development of educational units that are strategic and relevant to the community's needs. He has also successfully integrated high spiritual values with the demands of modernity, realized in a competitive formal educational institution. This success demonstrates that KH. Muwafiq possesses spiritual maturity and innovative leadership capable of maintaining the relevance and sustainability of the pesantren in the face of rapid social change dynamics.